Environment data processing for a Data Centre (1) - Tan, Eric Jiawei (Nanyang Technological University, 2023)
In the modern digital era, the increasing number of Data Centers (DCs) is a global trend driven by technological advancements. Alongside the escalating need for data storage and processing, the energy consumption of DCs is also on a steep rise. DCs are the one of the world’s greatest energy consumers. In tropical regions DC, substantial energy wastage is observed due to the continuous operation of electrical cooling systems aimed at controlling the DC’s temperature. Therefore, it becomes critical to investigate the environmental variables within DCs in these climates in order to enhance their management.